Educational trajectories of school graduates of the Russian industrial region - I. A. Aleshkovski; A. I. Moteva; N. E. Savina; A. T. Gasparishvili; O. V. Krukhmaleva (Obrazovanie i Nauka, 2020)
Introduction. The relevance of the research is accounted by the need to analyse the educational transition of youth from secondary schools to the tertiary education system and to develop a set of measures to encourage the majority of young people to stay in the region of residence and to aim at obtaining skills demanded by the local and regional labour market.The aim of the present research is to identify the educational plans of school graduates and the peculiarities of young people entering into a region’s higher education system. As indicators, the authors consider the availability of education and young people migration at the stage of transition from secondary education to higher education.The problematic situation consists in youth migration from the regions of residence to continue education in major university centers. It leads to a systemic change in the regions’ demographic situation and to the outflow of the most capable regional school leavers.Materials and research methods. The article is based on the data of the sociological study “Comprehensive Analysis of the Education System of the Kemerovo Region” conducted by the authors. A specially developed questionnaire using Google Forms platform was employed to interview the school graduates (787 ninth graders, 338 eleventh graders) and their parents (520 people). The survey covered 18 schools located in all types of settlements. At the stage of data analysis in the SPSS 25 functional environment, primary data were processed and the results were presented using descriptive statistics methods; an in-depth analysis of empirical information was carried out using multidimensional methods of analytical statistics, including the Pearson’s χ2 significance test, the procedures of factor, correlation and regression analysis (p < 0.001).Research results and scientific novelty. Long-range plans of secondary school graduates in the industrial region of Russia were identified; the motives in favour of their choice were studied; and the factors influencing this choice were revealed. As possible measures to overcome the outflow of young people from the regions, the authors propose to consider targeted training, the work with talented youth, the organisation of interaction at the level of “employer – school – university”, the various forms of network interaction of universities, as well as the modern forms of attracting students to the comfortable educational environment of the university, creating conditions not only for learning, but also for leisure, self-development, implementation of continuing education.Practical significance. The research results should be of use to specialists engaged in education studies and young people migration attitudes analysis, in labour market in Russia’s regions, to education management and regional administration officials. The research tools can be used in analysing educational migration and professional trajectories of secondary school graduates in Russia. The study is scheduled to be extended to other RF regions that are most troubled in terms of education migration, aiming to suggest possible ways to optimise this process there.